Paradigm Shifts in Contemporary Theology of Religions: Reconfiguring Religious Pluralism in the Twenty-First Century - David Ming (RaSAIL Media Group, Semarang, Indonesia, 2026)
This article investigates recent paradigm shifts in contemporary theology of religions amid the intensifying pluralism of the twenty-first century. The unit of analysis consists of academic works on the theology of religions, including peer-reviewed journal articles, scholarly books, and book chapters published primarily in the post-2000 period. The study aims to identify major intellectual developments in the field, examine how they reframe earlier typological models, and evaluate their implications for contemporary interreligious theology. Methodologically, the article employs a qualitative systematic literature review of selected publications from major academic databases, which were analyzed using thematic coding and interpretive synthesis. The review identifies four major shifts: from classical doctrinal typologies to practical-transformative pluralism; from universalist pluralism to comparative theology grounded in particular religious traditions; from liberal openness to postliberal and identity-conscious theological approaches; and from conventional interreligious concerns to new engagements with ecology, science, and digital religion. The article's novelty lies in its integrative mapping of these developments within a single analytical framework that connects doctrinal, dialogical, contextual, and public dimensions of the theology of religions. It contributes to contemporary scholarship by offering a clearer conceptualization of the field's current trajectories and by providing a foundation for more context-sensitive and globally relevant theological reflection in plural societies.